Isolated methylmalonic acidemia in Mexico: Genotypic spectrum, report of two novel MMUT variants and a possible synergistic heterozygosity effect - Cynthia Fernández-Lainez; Marcela Vela-Amieva; Miriam Reyna-Fabián; Liliana Fernández-Hernández; Sara Guillén-López; Lizbeth López-Mejía; Miguel Ángel Alcántara-Ortigoza; Ariadna González-del Angel; Rosa Itzel Carrillo-Nieto; Enrique Ortega-Valdez; Mauricio Rojas-Maruri; Cecilia Ridaura-Sanz (Molecular Genetics and Metabolism Reports)
Isolated methylmalonic acidemia (iMMA) is a group of monogenic metabolic disorders affecting methylmalonate and cobalamin metabolism. Five iMMA-responsible genes have been described to date: MMUT (MIM *609058), MMAA (MIM *607481, MMAB (MIM *607568), MMADHC (MIM *611935), and MCEE (MIM *608419). Although iMMA is the most common form of organic acidemia reported in Mexico, its genotypic spectrum is still largely unknown. We performed a clinical exome analysis on 42 unrelated Mexican patients with iMMA. MMUT deficiency accounted for 73.8 % of all cases, followed by MMAA (14.2 %), MMAB (7.2 %), and MMADHC (2.4 %) deficiencies. One patient presented MMUT and MMAA double heterozygosity, which should be further experimentally confirmed to prove that synergistic heterozygosity could be another inheritance mechanism in iMMA. The most frequent MMUT genotype involved the Hispanic variant NM_000255.4:c. [322C > T];[322C > T] or p.[Arg108Cys];[Arg108Cys] (14.3 %). Two novel MMUT variants, NM_000255.4:c.589G > A or p.(Ala197Thr) and c.1476C > A or p.(Tyr492*), were identified in a deceased newborn presenting the neonatal-onset severe form of the disease. In silico protein modeling of the p.(Arg108Cys) and novel p.(Ala197Thr) MMUT variants suggested disruption of the substrate-binding and catalytic domains of the protein, respectively. This study expands the current knowledge on the molecular spectrum of iMMA in the Mexican population and reinforces the importance of genetic analysis in guiding clinical management.